Climate change and its implications for human health - Cuadros Cagua, Tania Angélica (2018)
The purpose of this article is to analyze, employing a literature review, the effects of climate change on the health of people. To this end, we reviewed the scientific literature published on the consequences of climate change on human health and pointed out some of the effects secondary phenomena of climate change –such as extreme temperatures, heat waves, changes in the quality of air or water– have on the morbidity/mortality of the population. One of the conclusions of the study is that phenomena secondary to climate change have direct and indirect effects on human health, which gives rise to diverse and overlapping repercussions, with some others that will be difficult to reverse in years or decades.